O tempo de trabalho e o tempo livre dos professores municipais de Santa Maria/RS - Sagrillo, Daniele Rorato (2015)
This study versifies about the working time and the spare‟ time of municipal teachers from Santa Maria/RS. The objective of this study is to analyze and comprehend the time of teachers in the current configuration of the working world and of the educational reform. The dialectic historical materialism gives base to the study theoretical fundament. It consists in a mixed-method research using the Content Analysis and the IRAMUTEQ software as a support in the definition of the analysis categories. Three hundred twelve participants were obtained through questionnaire and other nine collaborators through the semi-structured interviews, during the year 2014. The results obtained prove the prolongation of the teachers‟ workload, contractual and paid, in and beyond the school space; the sub standardization and intensification of the teachers work; the destabilization of the teachers work with a stable‟ statute, among other aspects. It is concluded that in the reality observed it is not seen an interiorization between the life times, both qualified, complementary and necessary to the human being as constituting dimensions of being. However, an interiority ruled by the logic of the work intensification and sub standardization, in which times inter relate by invasion and the overlap of work and spare time, having available time to reach the extra class activity.